2020
DOI: 10.1186/s12888-020-2452-5
|View full text |Cite
|
Sign up to set email alerts
|

Exploring memory function in earthquake trauma survivors with resting-state fMRI and machine learning

Abstract: Background: Traumatized earthquake survivors may develop poor memory function. Resting-state functional magnetic resonance imaging (rs-fMRI) and machine learning techniques may one day aid the clinical assessment of individual psychiatric patients. This study aims to use machine learning with Rs-fMRI from the perspectives of neurophysiology and neuroimaging to explore the association between it and the individual memory function of trauma survivors. Methods: Rs-fMRI data was acquired for eighty-nine survivors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 79 publications
1
4
0
Order By: Relevance
“…Good performance on training data, with poor performance on test data, suggests overfitting, as most machine-learning studies are evaluated only on the basis of cross validation. Therefore, while our accuracy is relatively low (13), the strength of our methods and sample size support the importance of our findings. Conversely, the present results are comparable with machine-learning studies using large scale imaging datasets in other psychiatric disorders based on s-MRI data – 65% accuracy when classifying MDD from HC (9); 65.2% accuracy in differentiating patients with bipolar disorder and from controls (45); and a CV AUC of 0.57-0.61 when classifying cases as OCD or controls (52).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Good performance on training data, with poor performance on test data, suggests overfitting, as most machine-learning studies are evaluated only on the basis of cross validation. Therefore, while our accuracy is relatively low (13), the strength of our methods and sample size support the importance of our findings. Conversely, the present results are comparable with machine-learning studies using large scale imaging datasets in other psychiatric disorders based on s-MRI data – 65% accuracy when classifying MDD from HC (9); 65.2% accuracy in differentiating patients with bipolar disorder and from controls (45); and a CV AUC of 0.57-0.61 when classifying cases as OCD or controls (52).…”
Section: Discussionsupporting
confidence: 71%
“…Specifically, we rigorously tested the classification performance on both cross-validation AUC and test AUC, in which a fully independent portion of the data was left out when selecting the model (both architectures and parameters). We found relatively poor classification performance in classifying PTSD vs. controls (60% test AUC for s-MRI, 59% for rs-fMRI and 56% for d-MRI using SVM), which is lower than top-performing studies conducted at a single site, ranging between 55.56% (13) and 97.1% (14) for rs-fMRI, and between 73% (26) and 80% (29) for studies focusing on multimodal biomarkers. Yet, single-site studies show poor generalization to independent datasets (51), suggesting that performance might be adversely affected by small sample sizes, high-dimensional features, and use of complex models with a large number of parameters.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“… Cracco et al (2020) found preliminary evidence of dysfunctional spontaneous activity in adult women with experience of childhood abuse as participants showed hypoactivation of the right temporo-parietal junction during a spontaneous cognitive mentalizing task, a region commonly implicated in the individual’s “theory of mind” network (i.e., attributing states, beliefs, or perceptions to others). Using resting-state mean amplitude of spontaneous low-frequency fluctuation, Li et al (2020) found that visual working memory was negatively correlated with severity of PTSD symptoms of earthquake survivors. For individuals with PTSD, visual information processing may be impaired and declarative memory of visual information subsequently.…”
Section: Temporal Dynamics In Psychologymentioning
confidence: 99%
“…Another study also confirmed that lifetime PTSD affected about 10% of women and 5% of men in the general population (20,21). Moreover, a study focused on the nervous system and revealed the survivors' cognitive might decline, which might lead to loss of well-being in later life (22,23). In addition, according to the stress sensitization hypothesis, that individuals who have experienced previous PTSD are more susceptible to developing PTSD following subsequent traumas (24,25).…”
Section: Introductionmentioning
confidence: 99%